New metropolitan perspectives : local knowledge and innovation dynamics towards territory attractiveness through the implementation of Horizon/E2020/Agenda2030.: local knowledge and innovation dynamics towards territory attractiveness through the implementation of Horizon/E2020/Agenda2030. Volume 1 (2019) - Unknown
No abstract available